2021
DOI: 10.15537/smj.2021.42.7.20210348
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of COVID-19 antibodies among operating room and critical care staff at a tertiary teaching hospital

Abstract: Objectives: To identify the prevalence of COVID-19 antibodies among operating room and critical care staff. Methods:In this cross-sectional study, we recruited 319 Healthcare workers employed in the operation theater and intensive care unit of King Abdulaziz University Hospital (KAUH), a tertiary teaching hospital in Jeddah, Saudi Arabia between August 9, 2020 and November 2, 2020. All participants completed a 20-item questionnaire on demographic data and COVID-19 risk factors and provided blood samples. Antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 38 publications
4
11
0
Order By: Relevance
“…The source of SARS-CoV-2 infection among HCWs was mainly the community, with rates as high as 61.3% found in a study from Saudi Arabia and 25.5% in another study from Oman [22,23]. However, it is important to note that seroprevalence studies showed a low prevalence of 2.3% early in the pandemic, and this rate rose to 12.2% in another study [24,25]. It is interesting to note that the majority of HCWs were aware of the newly described Delta variant but had much less knowledge about the Delta-Plus variant, which could be explained by the media focusing on the Delta variant, previous study has shown Saudi students having satisfactory knowledge about the COVID-19 but poor knowledge about its mode of transmission and background of the disease highlighting the emphasis of further education and training especially for HCWs in our case about the dynamics of the disease rather than the media quality of knowledge [26][27][28][29].…”
Section: Discussionmentioning
confidence: 94%
“…The source of SARS-CoV-2 infection among HCWs was mainly the community, with rates as high as 61.3% found in a study from Saudi Arabia and 25.5% in another study from Oman [22,23]. However, it is important to note that seroprevalence studies showed a low prevalence of 2.3% early in the pandemic, and this rate rose to 12.2% in another study [24,25]. It is interesting to note that the majority of HCWs were aware of the newly described Delta variant but had much less knowledge about the Delta-Plus variant, which could be explained by the media focusing on the Delta variant, previous study has shown Saudi students having satisfactory knowledge about the COVID-19 but poor knowledge about its mode of transmission and background of the disease highlighting the emphasis of further education and training especially for HCWs in our case about the dynamics of the disease rather than the media quality of knowledge [26][27][28][29].…”
Section: Discussionmentioning
confidence: 94%
“…After publishing this paper, several other reports on the sero-status of COVID among healthcare workers started to appear [ 22 , 36 , 37 ]. Unlike the nationwide seroprevalence study discussed above, most of these studies were performed on healthcare workers from single hospitals with a relatively limited number of participants [ 22 , 36 ]. However, an added value for these studies was the diversity of serological assays utilized.…”
Section: Seroprevalence Status Among Healthcare Workersmentioning
confidence: 99%
“…Another study from our lab was performed on operating room and critical care staff and demonstrated a 12.2% sero-positivity rate [ 36 ]. The study period was between 9 August 2020 to 2 November 2020, which may explain the increase in the seroprevalence status [ 36 ].…”
Section: Seroprevalence Status Among Healthcare Workersmentioning
confidence: 99%
See 2 more Smart Citations